Warding off development: Local control, housing supply, and NIMBYs - Evan Mast (W.E. Upjohn Institute for Employment Research, 2020)
Local control of land-use regulation creates a not-in-my-backyard (NIMBY) problem that can suppress housing construction, contributing to rising prices and potentially slowing economic growth. I study how increased local control affects housing production by exploiting a common electoral reform-changing from "at-large" to "ward" elections for town council. These reforms, which are not typically motivated by housing markets, shrink each representative's constituency from the entire town to one ward. Difference-in-differences estimates show that this decentralization decreases housing units permitted by 24 percent, with 47 percent and 12 percent effects on multi- and single-family units. The effect on multifamily is larger in high-homeownership towns.
Keywords: R31; R38; H77; 330; Housing supply; land-use regulation; NIMBYism